The Analysis of Translation Method of Song Lyric “White Flag” by Dido - Dewi Wulandari (CV. AFDIFAL MAJU BERKAH, 2025)
This study aims to analyze the translation method of Dido's song lyrics“White Flag” by using Peter Newmark's translation theory. In this theory, there are eight translation strategies, but this study focuses on three main strategies, namely semantic, faithful, and communicative translation. Five song lyric data were selected to be analyzed based on the application of these three strategies. Semantic translation emphasizes faithfulness to the original meaning of the source text, faithful translation emphasizes more on maintaining the structure and style of the original language, while communicative translation focuses on adaptation so that the message can be understood by the target audience. The research approach is descriptive qualitative, by analyzing the lyric data translated through the three strategies. The result of the research shows that faithful translation is a method that is often used in translating the lyrics of the song “White Flag”. This can be seen in the attempt to maintain the structure, style, and emotional nuances of the original lyrics. However, semantic and semantic and communicative strategies are also used in certain parts to ensure the meaning of the lyrics is maintained and relevant to Indonesian-speaking listeners. This research contributes to understanding of the application of Newmark's theory in the translation of song lyrics and provides insights into how faithfulness to the source text can be prioritized in the translation of musical literature.